2017
DOI: 10.1111/jnu.12356
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Gender Pay Differentials in the New Millennium

Abstract: Background: The gender pay gap in the United States is an ongoing issue, affecting women in nearly all occupations. Jobs traditionally associated with men tend to pay better than traditionally female-dominated jobs, and there is evidence to suggest within-occupation gender pay differences as well. Purpose: We compared and contrasted gender wage disparities for registered nurses (RNs), relative to gender wage disparities for another female-dominated occupation, teachers, while controlling for sociodemographic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 15 publications
2
32
0
Order By: Relevance
“…These results are consistent with what Cohen and Huffman reported about female managers associated with lower gender wage gaps, especially when those women were in managerial positions of relatively high status [53]. However, other studies indicated that in many institutions worldwide, women are still extremely underrepresented in leadership positions and also have access to lower salaries on average than their male peers [64][65][66][67].…”
Section: Discussionsupporting
confidence: 89%
“…These results are consistent with what Cohen and Huffman reported about female managers associated with lower gender wage gaps, especially when those women were in managerial positions of relatively high status [53]. However, other studies indicated that in many institutions worldwide, women are still extremely underrepresented in leadership positions and also have access to lower salaries on average than their male peers [64][65][66][67].…”
Section: Discussionsupporting
confidence: 89%
“…Male nurses in the United States believe that they have many career opportunities (Moore & Dienemann, 2013) and an analysis of national employment data revealed that there was equal representation of males and females in nursing supervisory positions (Snyder & Green, 2008). However, there is a gender pay gap between male and female nurses with male nurses earning more than female nurses (Muench, Sindelar, Busch, & Buerhaus, 2015;Snyder & Green, 2008;Wilson, Butler, Butler, & Johnson, 2017).…”
Section: Male N Ur S E S' Accep Tan Ce and Satis Fac Ti On In The Wmentioning
confidence: 99%
“…Most of the nurse supervisors were female (87.5%), which supported by Wilson et al (2018) statement that the nursing profession is female-dominated work (5). The study by Wilson et al (2018) also documented findings that the nurse was viewed as a caring profession so as women fit for the job due to their motherly instinct (5). In the presense of this limelight, men were driven away to choose nursing as their profession.…”
Section: Discussionmentioning
confidence: 72%
“…This implies according to the study of Zwick that younger supervisors are frequently associated with technical skills and knowledge, innovation, creativity, flexible to work schedules and is open to new knowledge (4). Most of the nurse supervisors were female (87.5%), which supported by Wilson et al (2018) statement that the nursing profession is female-dominated work (5). The study by Wilson et al (2018) also documented findings that the nurse was viewed as a caring profession so as women fit for the job due to their motherly instinct (5).…”
Section: Discussionmentioning
confidence: 97%